Two for the dough - Evanovich, Janet (Evanovich, Janet. Stephanie Plum novel, 1996)
Armed with attitude, not to mention stun gun, defense spray, killer flashlight and her mistrusted .38, Stephanie Plum, the bounty hunter from Trenton, New Jersey, goes after a man who skipped bail. He replies by taunting her in a gruesome manner, sending her bits and pieces of dead people. By the author of One for the Money.